Dynamic modeling and validation of a liquid desiccant cooling and dehumidification system - Ou, Xianhua (2018)
In this study, a simplified dynamic model for the liquid desiccant cooling and dehumidification system (LDCDS) is developed from a control viewpoint based on the laws of conservation of energy and mass. The complete LDCDS consists of three subsystems, namely the cooling coil, dehumidifier and cooler in which the models can be estimated separately and combined to obtain the model of LDCDS. The heat and mass transfer rates in model are derived through effectiveness-NTU and hybrid modeling approaches. The parameters of the thermal and moisture dynamic models are pre-identified by using the Levenberg–Marquardt method with static experimental data from the LDCDS pilot plant and then refined by adopting an unscented Kalman filter algorithm with dynamic experimental data. Detailed experimental tests on a pilot plant reveal that the proposed model accurately predicts the system performance under different operating conditions. The proposed model is expected to be applied in further research on the effects of more advanced control and optimization algorithms with the system energy efficiency.